2015
DOI: 10.1088/1748-0221/10/07/p07009
|View full text |Cite
|
Sign up to set email alerts
|

Laser-plasma X-ray detection by using fast 4H-SiC interdigit and ion collector detectors

Abstract: Non-equilibrium plasma generated by nanosecond pulsed laser are characterized by solid state 4H-SiC interdigit Schottky diodes and by a large area ion collector detector, both connected in time-of-flight configuration. Plasma generated by irradiation of different metallic targets through a pulsed laser with a 1010 W/cm2 intensity and a 200 mJ energy, where monitored. In this paper we demonstrate that the interdigit 4H-SiC diode is able to detect ultraviolet radiation and soft X-rays, with energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…All these properties make SiC an ideal material for high-power and high-frequency devices and, more generally, for the fabrication of harsh-environment electronics [ 2 , 3 ]. Other properties such as biocompatibility, visible blindness, and radiation hardness make this material attractive for alternative applications, such as biomedical sensors, as well as for UV and X-ray functions, charged particle detectors [ 4 , 5 , 6 , 7 ], and also for uses involving visible radiation presences, such as plasma environments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these properties make SiC an ideal material for high-power and high-frequency devices and, more generally, for the fabrication of harsh-environment electronics [ 2 , 3 ]. Other properties such as biocompatibility, visible blindness, and radiation hardness make this material attractive for alternative applications, such as biomedical sensors, as well as for UV and X-ray functions, charged particle detectors [ 4 , 5 , 6 , 7 ], and also for uses involving visible radiation presences, such as plasma environments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, the reverse current is about 2 pA at 10-V reverse bias, more than two orders of magnitude lower with respect to silicon Schottky diodes, permitting to obtain high detection sensitivity [11], [18].…”
Section: Methodsmentioning
confidence: 99%
“…The plasma monitoring generally uses ion collectors (ICs), ion energy analyzers (IEAs), Langmuir probes (LPs), and optical spectroscopy (OS). These permit to measure the ion current, the ion charge state distribution, the plasma temperature, and density and their evolution with the time [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other properties such as the transparency to visible light, the UV-photons absorption, the radiation hardness, and the biocompatibility make this material attractive for alternative applications, for instance, biomedical sensors and X-ray, UV, and charged particles detectors [ 4 , 5 , 6 , 7 ]. Applications involve visible light and hostile environment such as, for example, the monitoring of laser generated plasma or of flames in industrial apparatus found large prominence [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%